An approach for 2D modelling of laterally loaded piles (2023)
Despite a considerable progress in the analysis and design of monopiles, many methods are based on complex mathematical structures with doubtful or hard assumptions to verify. Therefore, there is still a need for simple and yet accurate methods for the analysis of monopiles under drained and undrained lateral cyclic loading conditions. In this work, a simple yet efficient two-dimensional modelling approach for the analysis of monopiles is proposed. To account for out-of-plane frictional forces, counter-forces derived from virtual frictional forces generated at the out-of-plane pile interface are applied along the pile length together with the scaled pile stiffness. The predictive capabilities of the proposed approach were validated by back-calculating two different experimental sets. The first consists of a small-scale field monopile test on a coarse-grained soil subjected to lateral cyclic loading under drained conditions. The second is a centrifuge test involving a fine-grained soil subjected to lateral cyclic loading under practically undrained conditions. Simulation results with the proposed approach suggest an accurate prediction of pile displacements and bending moments under both drained and undrained lateral cyclic conditions. The method is, however, unable to reproduce pore water pressures generated behind the pile in low permeability materials.